Digital economic security of Russian organizations, industries and Russia as a whole - S. A. Antonov; A. V. Savchenko; O. G. Kazeeva (Вестник университета)
The challenge of modern threats to the digital economic security of organizations of the Russian Federation in the conditions of widespread application of digital technologies has been considered. The strategic goals, defined in the "Digital program of the Russian Federation " have been analyzed. The logical and functional contradictions of the concepts, related to the digital economy, used in normative documents, have been examined. The applicability in the analysis of threats of S. Mann’s "chaos theory" has been substantiated. The main priority direction of the Russian digital economy has been defined - the protection of the national digital market and reducing Russia’s digital dependence on digital imports. Other critical, practically significant conclusions and a proposal for the organization offurther research have been formulated.